Uncovering the First Atypical DS-1-like G1P[8] Rotavirus Strains That Circulated during Pre-Rotavirus Vaccine Introduction Era in South Africa - Mwangi, Peter N.; Mogotsi, Milton T.; Rasebotsa, Sebotsana P.; Seheri, Mapaseka L.; Mphahlele, M. Jeffrey; Ndze, Valantine N.; Dennis, Francis E.; Jere, Khuzwayo C.; Nyaga, Martin M. (Pathogens (Basel), 2020)
Emergence of DS-1-like G1P[8] group A rotavirus (RVA) strains during post-rotavirus vaccination period has recently been reported in several countries. This study demonstrates, for the first time, rare atypical DS-1-like G1P[8] RVA strains that circulated in 2008 during pre-vaccine era in South Africa. Rotavirus positive samples were subjected to whole-genome sequencing. Two G1P[8] strains (RVA/Human-wt/ZAF/UFS-NGS-MRC-DPRU1971/2008/G1P[8] and RVA/Human-wt/ZAF/UFS-NGS-MRC-DPRU1973/2008/G1P[8]) possessed a DS-1-like genome constellation background (I2-R2-C2-M2-A2-N2-T2-E2-H2). The outer VP4 and VP7 capsid genes of the two South African G1P[8] strains had the highest nucleotide (amino acid) nt (aa) identities of 99.6–99.9% (99.1–100%) with the VP4 and the VP7 genes of a locally circulating South African strain, RVA/Human-wt/ZAF/MRC-DPRU1039/2008/G1P[8]. All the internal backbone genes (VP1–VP3, VP6, and NSP1-NSP5) had the highest nt (aa) identities with cognate internal genes of another locally circulating South African strain, RVA/Human-wt/ZAF/MRC-DPRU2344/2008/G2P[6]. The two study strains emerged through reassortment mechanism involving locally circulating South African strains, as they were distinctly unrelated to other reported atypical G1P[8] strains. The identification of these G1P[8] double-gene reassortants during the pre-vaccination period strongly supports natural RVA evolutionary mechanisms of the RVA genome. There is a need to maintain long-term whole-genome surveillance to monitor such atypical strains.